Confidence is good; too much, not so much: Exploring the effects on reward-based crowdfunding success - Naomi Moy; Ho Fai Chan; Frank Mathmann; Markus Schaffner; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Self-confidence has long been regarded as one of the key qualities in determining entrepreneurial success. In markets with uncertainty, like crowdfunding, entrepreneurial confidence is an important signal that lowers the information imbalance for potential investors. However, current literature on confidence is limited in three ways; first is the limited understanding of confidence in interpersonal interactions; second is the accurate measurement of confidence and thirdly, limited insight on whether an optimal level of confidence exists. We use two novel behavioral approaches to measure self and exhibited confidence and examine their relation to entrepreneurial success in reward-based crowdfunding. Derived from ex-ante information (i.e., before realization of success), our measurements for confidence allow us to draw causal inferences, allowing for contributions to confidence and displays of interpersonal emotion literature. By analyzing over 70,000 Kickstarter projects, we show an optimal level of entrepreneurial confidence exists in determining funding received, popularity, and likelihood of success.
Keywords: 330; Behavioral; crowdfunding; entrepreneur; exhibiting confidence; interpersonal confidence; success